Comparison of Stability And Sternum Healing Rate in Clinical and Ultrasonography (USG) between Stainless Steel Wire and Polydioxanone Yarn in Children Heart Surgery Operation - Prima Kharisma Hayuningrat1, Heroe Soebroto1, Paulus Rahardjo2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The closing of the sternum bone is often used today by using stainless steel wire material and Polydioxanone yarn continuous suture. To objectives to be achieved for sternal healing after heart surgery without complications resulting from the failure of sternal healing. The bone healing process itself is influenced by mechanical stress and movement. Objectives: To compare the effects of sternum closure techniques on surgical patients The heart of the child uses Polydioxanone and Stainless Steel Wire threads against clinical stability and rate of healing which are evaluated clinically and Ultrasonography. Methods: Performed sternal closure of pediatric patients after cardiac surgery with sternal wire (n = 8) and PDS (n = 8). Performed sternal pain and stability evaluation with the physical examination. Further sternum ultrasonographyund was performed to assess displacement, gap and callus picture. Evaluations were performed at weeks 6, 9 and 12 postoperatively. Results: Week 6 and 9 degrees of pain were higher in sternal wire compared with polydioxanone (p = 0.03 and p = 0.01). The 12th week of sternal wire and polydioxanone did not find any difference in pain (p = 1,000). Week 6, 9 and 12 there was no clinical stability difference between wire and PDS (p = 0.143, p = 0.264, p = 0.063). 9th, 9th and 12th Sternum ultrasonography of examination appears to be displacement in polydioxanone (p = 0.025, p = 0.009, p = 0.009). The gap increased significantly from 6th to 9th weeks in the polydioxanone group, while the addition at week 9 to 12 was statistically insignificant but it appears that polydioxanone had a wider gap addition range than the sternal wire. Week 9 and 12 callus were seen more often in sternal wire patients but not significant (P = 0.602, p = 0.333) Conclusion: Clinically, sternal steal wire stability is proportional to polydioxanone. Radiologically, the stability of sternal wire is better than polydioxanone. The rate of sternal cure in polydioxanone is proportional to the sternal wire.